Proliferative and Osteogenic Supportive Effect of VEGF-Loaded Collagen-Chitosan Hydrogel System in Bone Marrow Derived Mesenchymal Stem Cells - Jeevithan Elango (MDPI AG, 2023)
The use of hydrogel (HG) in regenerative medicine is an emerging field and thus several approaches have been proposed recently to find an appropriate hydrogel system. In this sense, this study developed a novel HG system using collagen, chitosan, and VEGF composites for culturing mesenchymal stem cells (MSCs), and investigated their ability for osteogenic differentiation and mineral deposition. Our results showed that the HG loaded with 100 ng/mL VEGF (HG-100) significantly supported the proliferation of undifferentiated MSCs, the fibrillary filament structure (HE stain), mineralization (alizarin red S and von Kossa stain), alkaline phosphatase, and the osteogenesis of differentiated MSCs compared to other hydrogels (loaded with 25 and 50 ng/mL VEGF) and control (without hydrogel). HG-100 showed a higher VEGF releasing rate from day 3 to day 7 than other HGs, which substantially supports the proliferative and osteogenic properties of HG-100. However, the HGs did not increase the cell growth in differentiated MSCs on days 14 and 21 due to the confluence state (reach stationary phase) and cell loading ability, regardless of the VEGF content. Similarly, the HGs alone did not stimulate the osteogenesis of MSCs; however, they increased the osteogenic ability of MSCs in presence of osteogenic supplements. Accordingly, a fabricated HG with VEGF could be used as an appropriate system to culture stem cells for bone and dental regeneration.